Depolarization-Induced Calcium-Independent Synaptic Vesicle Exo- and Endocytosis at Frog Motor Nerve Terminals - Abdrakhmanov, M.M. (A.I. Gordeyev, 2013)
The transmitter release and synaptic vesicle exo- and endocytosis induced by constant current depolarization of nerve terminals were studied by microelectode extracellular recording of miniature endplate currents and fluorescent microscopy (FM 1-43 styryl dye). Depolarization of the plasma membrane of nerve terminals in the control specimen was shown to significantly increase the MEPC frequency (quantal transmitter release) and exocytotic rate (FM 1-43 unloading from the synaptic vesicles preliminarily stained with the dye), which was caused by a rise in the intracellular Ca(2+) concentration due to opening of voltage-gated Ca channels. A slight increase in the MEPC frequency and in the rate of synaptic vesicle exocytosis was observed under depolarization in case of blockade of Ca channels and chelating of intracellular Ca(2+) ions (cooperative action of Cd(2+) and EGTA-AM). The processes of synaptic vesicle endocytosis (FM 1-43 loading) were proportional to the number of synaptic vesicles that had undergone exocytosis both in the control and in case of cooperative action of Cd(2+) and EGTA-AM. A hypothesis has been put forward that Ca-independent synaptic vesicle exo- and endocytosis that can be induced directly by depolarization of the membrane exists in the frog motor terminal in addition to the conventional Ca-dependent process.